The Nursing Documentation Dilemma in Uganda: Neglected but Necessary. A Case Study at Mulago National Referral Hospital - Nakate, Grace; Dahl, Diane; Petrucka, Pammla; Drake, Karen B. (Open Journal of Nursing, 2015)
In Uganda, nursing documentation still remains a challenge, in most of the government hospitals and some private hospitals, it remains at a manual (non-technology driven) level and omissions have been observed. Nurses continue to capture standard elements in their documentation. A mixed methods intervention study was conducted to determine knowledge and attitudes of nurses towards documentation, including an evaluation of nurses’ response to a designed nursing documentation form. Forty participants were selected through convenience sampling from six wards of a Ugandan health institution. The study intervention involved teaching nurses the importance of documentation and using of the trial documentation tool. Pre- and post-testing and open-ended questionnaires were used in data collection. The results from the close-ended questions were presented in the previous publication; the responses from the open-ended questions would then be presented. The open-ended questions regarding comments about the nursing documentation process and suggestions about the process of implementing the nursing documentation system in the ward units were considered. All participants were provided the opportunity to provide personal comments, reflections, or stories of their experiences with documentation in patient care. A thematic analysis approach was used during data analysis. The results showed that the participants had positive attitude towards documentation of patient care, but they had constraints limiting them to document, they reflected issues concerning the perceived pressure from the administrations and support to document. The study findings have implication that there is need for organizational support and to have multisite studies and extension of the documentation tool.
Keywords: Nursing Documentation, Qualitative Researcher, Nursing Records, Uganda Healthca